Atomically Thin Antimony‐Doped Indium Oxide Nanosheets for Optoelectronics. Issue 20 (14th July 2022) - Nguyen, Chung Kim; Low, Mei Xian; Zavabeti, Ali; Murdoch, Billy J.; Guo, Xiangyang; Aukarasereenont, Patjaree; Mazumder, Aishani; Dubey, Aditya; Jannat, Azmira; Rahman, Md. Ataur; Chiang, Ken; Truong, Vi Khanh; et al.
Abstract: Wide bandgap semiconducting oxides are emerging as potential 2D materials for transparent electronics and optoelectronics. This fuels the quest for discovering new 2D metal oxides with ultrahigh transparency and high mobility. While the former can be achieved by reducing the thickness of oxide films to only a few nanometers, the latter is more commonly realized by intentional doping. This article reports a one‐step synthesis of few‐unit‐cell‐thick and laterally large antimony‐doped indium oxide (IAO). The doping process occurs spontaneously when the oxide is grown on the surface of a molten Sb–In alloy and 2D IAO nanosheets can be easily printed onto desired substrates. With thicknesses at the atomic scale, these materials exhibit excellent transparency exceeding 98% across the visible and near‐infrared range. Field‐effect transistors based on low‐doped IAO nanosheets reveal a high electron mobility of ≈40 cm 2 V −1 s −1 . Additionally, a notable photoresponse is observed in 2D IAO‐based photodetectors under ultraviolet (UV) radiation. Photoresponsivities of low‐doped and highly doped IAO at a wavelength of 285 nm are found to be 1.2 × 10 3 and 0.7 × 10 3 A W −1, respectively, identifying these materials as promising candidates for the fabrication of high‐performance optoelectronics in the UV region. Abstract : 2D crystalline antimony‐doped indium oxide nanosheets with few‐atom thicknesses and laterally large dimensions are synthesized utilizing a single‐step, scalable liquid metal printing technique. The work proposes a viable pathway for realizing ultrathin transparent semiconducting oxides with enhanced electronic and optical properties, providing a fascinating semiconducting platform for next‐generation optoelectronics, neuromorphic devices, and beyond.